Barriers to Child Success in School: A Critical Focus on Child Neglect and Academic Performance of Pupils in the Bantama Community in Kumasi, Ghana - Badu, Eric; Opoku, Maxwell Peprah; Amponsah, Appiah-Danquah K (ATIKAN, 2015)
ABSTRACT: The child neglect seems to increase students suffering and substantially affect their academic performance. This study aimed to investigate the effect of child neglect on academic performance of JHS (Junior High School) pupil in the Bantama community in Kumasi, Ghana. A cross sectional survey with quantitative methods was conducted with pupils within the Bantama community. A purposive sampling was used to select four community schools: Kookoase JHS, Presbyterian JHS, Bantama Methodist, and Roman Catholic JHS. A simple random sampling was used to select 200 pupils. The common child neglect experienced by pupils was lack of parental supervision, encouragement, and basic necessities. The study found that most pupils lacked educational materials, including books, funds for extra classes, and school uniforms. The study found a significant association between child neglect and academic performance of pupils, such that child neglect positively correlated with poor academic performance (r = 0.77; p = 0.02). The study findings suggest that pupils experienced child neglect which affects their ability to perform in school. It is recommended that parental contribution in resourcing students with the necessary provisions will improve their academic performance.KEY WORD: Education; Child Neglect; Junior High School; Academic Performance; Parental Supervision.Â RINGKASAN: âHambatan untuk Sukses Anak di Sekolah: Sorotan Kritis tentang Pengabaian Anak dan Prestasi Akademik Siswa pada Masyarakat Bantama di Kumasi, Ghanaâ. Mengabaikan anak tampaknya meningkatkan penderitaan para siswa dan secara substansial mempengaruhi prestasi akademik mereka. Penelitian ini bertujuan untuk mengetahui pengaruh mengabaikan anak terhadap prestasi akademik siswa SMP (Sekolah Menengah Pertama) pada masyarakat Bantama di Kumasi, Ghana. Sebuah survei silang dengan metode kuantitatif dilakukan terhadap para siswa dalam masyarakat Bantama. Sampel bertujuan digunakan untuk memilih empat sekolah, yakni: SMP Kookoase, SMP Presbyterian, SMP Methodist Bantama, dan SMP Katolik Roma. Sampel acak sederhana digunakan untuk memilih 200 siswa. Pengabaian anak secara umum yang dialami oleh murid adalah kurangnya pengawasan orangtua, dorongan semangat, dan pemenuhan kebutuhan dasar. Studi ini menemukan bahwa sebagian besar siswa tidak memiliki bahan pendidikan, termasuk buku, dana untuk kelas tambahan, dan seragam sekolah. Studi ini menemukan hubungan yang signifikan antara mengabaikan anak dan prestasi akademik siswa, sehingga mengabaikan anak berkorelasi positif dengan prestasi akademik yang buruk (r = 0.77; p = 0.02). Temuan penelitian menunjukan bahwa siswa yang mengalami pengabaian mempengaruhi kemampuan mereka dalam unjuk kinerja di sekolah. Disarankan bahwa kontribusi orangtua dalam melengkapi para siswa dengan ketentuan yang diperlukan akan meningkatkan prestasi akademik mereka.KATA KUNCI: Pendidikan; Mengabaikan Anak; Sekolah Menengah Pertama; Prestasi Akademik; Pengawasan Orangtua.Â Â Â Â About the Authors: Eric Badu and Maxwell Peprah Opoku are the Lecturers at the Centre for Disability and Rehabilitation Studies KNUST (Kwame Nkrumah University of Science and Technology), Private Mail Bag, Knust-Kumasi, Ghana. Appiah-Danquah K. Amponsah is a Lecturer at the Department of Sociology and Social Work KNUST, Private Mail Bag, Knust-Kumasi, Ghana. Corresponding author is: abizep4@yahoo.comHow to cite this article? Badu, Eric, Maxwell Peprah Opoku & Appiah-Danquah K. Amponsah. (2015). âBarriers to Child Success in School: A Critical Focus on Child Neglect and Academic Performance of Pupils in the Bantama Community in Kumasi, Ghanaâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.5(2) December, pp.133-142. Bandung, Indonesia: Minda Masagi Press, ISSN 2088-1290.Chronicle of the article: Accepted (October 28, 2015); Revised (November 25, 2015); and Published (December 30, 2015).